Pemberdayaan Buruh Migran melalui Program Desa Migran Produktif di Banyumas, Indonesia: Migrant Workers Empowerment through Productive Migrant Village Programs in Banyumas, Indonesia - Muslihudin Muslihudin; Tyas Retno Wulan; Tri Sugiarto; Sotyania Wardhianna; Sri Wijayanti (Society, 2021)
This study explains empowering Indonesian Migrant Workers (IMW) through Productive Migrant Village Programs (PMVP) in the Banyumas Regency. PMVP is a program of the Ministry of Manpower of the Republic of Indonesia held since 2016. The program aims are to empower, improve services and protection for IMWs starting from the village. The paradigm of the study is a constructivist paradigm by using a critical model. The research method used is a qualitative method with a phenomenological approach, which explores data to get the meaning of the basic and essential things of the empirical phenomena experienced by the research subject. The results of the research are 1). In providing information about the process of migrant workers faced with challenges from recruitment agencies/recruitment companies (Private Indonesian Migrant Worker Placement Agency). 2). In the stage of the production process, there are obstacles that the equipment provided by the Ministry cannot use. 3). The care of children of migrant workers is still individual only to their families. The community even still stigmatizes them as children who deserve problems since their parents abandoned them. 4). Late initiation of the migrant workers’ cooperatives. Procedures for establishing migrant workers cooperatives, mentoring, and guidance specifically related to migrant workers are needed.